A Non‐Precious‐Metal Catalyst Derived from a Cp2‐Co+‐PBI Composite for Cathodic Oxygen Reduction under Both Acidic and Alkaline Conditions. Issue 5 (28th February 2017) - Zhu, Hong; Sun, Zhaonan; Chen, Nanjun; Cao, Hehuan; Chen, Minglin; Li, Ke; Cai, Yezheng; Wang, Fanghui
Abstract: One major limitation for polymer electrolyte membrane fuel cells is the sluggish cathode kinetics. Development of efficient noble‐free catalysts is the key resolution to the problem of the oxygen reduction reaction (ORR) in both acid and alkaline solutions. Herein, we report a new type of efficient non‐precious‐metal catalyst for the ORR through the direct pyrolysis of poly[2, 2′‐(1, 1′‐cobaltocenium)‐5, 5′‐dibenzimidazole]. The cobalt oxides were produced after pyrolysis at 900 °C (Cp2 ‐Co + ‐PBI‐900, where PBI is polybenzimidazole). The obtained catalysts exhibit higher electrocatalytic activity and stability for the ORR under both alkaline and acidic conditions. Structural characterization manifested that Cp2 ‐Co + ‐PBI‐800 had the highest graphitic N content and Cp2 ‐Co + ‐PBI‐900 was also produced. In alkaline media, Cp2 ‐Co + ‐PBI‐900 showed the highest ORR activity with onset potential of 998 mV (vs. RHE), which was only 22 mV higher than that of Pt/C under identical conditions. Besides, in acidic media, Cp2 ‐Co + ‐PBI‐800 exhibited excellent ORR activity with an onset potential of 847 mV (vs. RHE) after leaching in 6 M HCl solution for 12 h. Both optimal catalysts displayed high durability, especially in acidic media. The half‐wave potential was also improved by 11 mV after 5000 CV scanning cycles in N2 . The catalysts possessed diverse active sites in different working conditions. In acid conditions, cobalt acted as the promotor, whereas, in alkaline conditions, CoO was the activity site. Moreover, graphite N and pyridine N were the main activity sites in acid and alkaline conditions, respectively. PBI has a long‐chain and π‐conjugated system, indicating that the PBI precursor can be used as a non‐precious‐metal catalyst. Abstract : A question of nobility : A poly[2, 2′‐(1, 1′‐cobaltocenium)‐5, 5′‐dibenzimidazole] precursor can be used as a unique repetition structure, leading to homo‐dispersed cobalt compounds after high‐temperature pyrolysis. A polymer structure with two imidazoles and one Co + in each unit can be used as an integration catalyst after pyrolysis, and this homo‐dispersed structure can expose more active sites to reach a high performance.